Isolation and identification of one pigeon-origin Gallibacterium genomo sp. 3 - Yang Xiaolin; Chen Ying; Yu Songcheng; Zou Nianli; Wu Ruiting; Xia Jing; Niu Ting; Wang Fuyan; Huang Yong (浙江大学学报. 农业与生命科学版)
Gallibacterium infection was a new infectious disease observed in some areas of China, which was mainly harmful for laying hen, resulting in salpingitis, oophoritis, peritonitis, septicemia, hepatitis, enteritis, respiratory tract diseases, and so on. So far, most of the G. anatis were isolated from poultry, including chickens, ducks, pigeons, geese, parrots, quail and guinea fowl, etc. Isolation of Gallibacterium from pigeons was not reported in China.A contagious disease occurred in one breeding farm of pigeon in Sichuan Province in January of 2013, with the characteristic signs of depressed wasting, dyspnea, diarrhea, and so on. The morbidity was about 43%, and the mortality was about 18%. The disease was mainly found in female pigeons, and female pigeons of different ages could be infected, especially pigeons of 1 to 1.5 years old. Mild bleeding and mucus could be observed in diseased pigeons, and other gross lesions could also be observed including hemorrhage of lung, peritonitis, salpingitis, mild bleeding of duodenum, and so on. This disease had caused great economic losses to the pigeon farm. In order to propose a proper treatment program for this disease, representative samples were collected from disease pigeons for bacteria isolation and virus detection.The bacteria were isolated by blood agar and were identified by following test: morphological observation, biochemical identification, animal experiment, antibiotic sensitive experiment, 16S rRNA gene sequence analysis. Animal experiments were conducted by infecting mice and pigeons to observe its pathogenicity. For the virus detection, the nucleotide sequences of infectious bronchitis virus (IBV), avian influenza virus subtype (H9N2) and Newcastle disease virus (NDV) were detected by RT-PCR.The results showed that NDV was detected from the lung and trachea of some sick pigeons, and one bacterial strain was isolated from the livers and lungs of sick pigeons and named as SC01. The SC01 strain was gram-negative (G-), short rod-shaped bacteria. It was pathogenic to mice, and the median lethal dose to mice was 1.26 × 109 CFU/mL. Biochemical test showed that it can ferment most sugars and alcohols. Sensitive drug screen revealed that the SC01 strain was sensitive to ceftriaxone sodium, cefoperazone sodium, florfenicol, cephalexin, cefazolin, and resistant to neomycin, streptomycin, erythromycin, sulfafurazole, etc. The 16S rRNA gene sequence of the SC01 strain was blasted in GenBank, and the results showed that the nucleotide sequence homologies of SC01 and Gallibacterium, Pasteurella, Haemophilus, Actinobacillus were relatively high. The 16S rRNA nucleotide sequence homologies of SC01 and four G. genomo sp.3 strains were 98.5% 99.5%, and the highest homology (99.5%) came from the comparison between the sequences of SC01 and EU423996. Phylogenetic analysis showed that SC01 strain and nine Gallibacterium strains formed an independent big branch in phylogenetic tree. The SC01 strain and G. genomo sp. 3 fell into the same small branch. Meanwhile, Pasteurella, Haemophilus and Actinobacillus formed another big branch in phylogenetic tree.In conclusion, a G. genomo sp. 3 was isolated from diseased pigeons, and its biological character, pathogenicity, drug sensitivity and 16S rRNA sequence were also analyzed. The results provide an important reference for the epidemiological investigation, diagnosis and therapy of G. genomo sp.3 infection in China. In addition, the appearance of G. genomo sp.3 infection in pigeons may provide a new challenge for the prevention and therapy of pigeon disease in China.